Testis exposure to unopposed/elevated activin A in utero affects somatic and germ cells and alters steroid levels mimicking phthalate exposure - Whiley, Penny A. F.; Luu, Michael C. M.; O’Donnell, Liza; Handelsman, David J.; Loveland, Kate L. (Frontiers in Endocrinology, 2023)
Correct fetal testis development underpins adult male fertility, and TGFβ superfamily ligands control key aspects of this process. Transcripts encoding one such ligand, activin A, is upregulated in testes after sex determination and remains high until after birth. Testis development requires activin signalling; mice lacking activin A (Inhba KO) display altered somatic and germ cell proliferation, disrupted cord elongation and altered steroid synthesis.In human pregnancies with pre-eclampsia, the foetus is inappropriately exposed to elevated activin A. To learn how this affects testis development, we examined mice lacking the potent activin inhibitor, inhibin, (Inha KO) at E13.5, E15.5 and PND0. At E13.5, testes appeared similar in WT and KO littermates, however E15.5 Inha KO testes displayed two germline phenotypes: (1) multinucleated germ cells within cords, and (2) germ cells outside of cords, both of which are documented following in utero exposure to endocrine disrupting phthalates in rodents. Quantitation of Sertoli and germ cell in Inha KO (modelling elevated activin A) and Inhba KO (low activin A) testes using immunofluorescence demonstrated activin A bioactivity determines the Sertoli/germ cell ratio. The 50% reduction in gonocytes in Inha KO testes at birth indicates unopposed activin A has a profound impact on embryonic germ cells. Whole testis RNAseq on Inha KO mice revealed most transcripts affected at E13.5 were present in Leydig cells and associated with steroid biosynthesis/metabolism. In agreement, androstenedione (A4), testosterone (T), and the A4:T ratio were reduced in Inha KO testes at E17.5, confirming unopposed activin A disrupts testicular steroid production. E15.5 testes cultured with either activin A and/or mono-2ethylhexyl phthalate (MEHP), generated common histological and transcriptional outcomes affecting germline and Leydig cells, recapitulating the phenotype observed in Inha KO testes. Cultures with activin A and MEHP together provided evidence of common targets.Lastly, this study extends previous work focussed on the Inhba KO model produce a signature of activin A bioactivity in the fetal testis. These outcomes show the potential for elevated activin A signalling to replicate some aspects of fetal phthalate exposure prior to the masculinization programming window, influencing fetal testis growth and increasing the risk of testicular dysgenesis.